(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, in the era of renewing Uzbekistan, it is stated that the spiritual, educational, social, economic and legal basis for increasing the socio-political and social activity of women, strengthening their abilities and opportunities in various fields and industries, family stability, protecting the legal interests of women, issues of wide use of the opportunities created in the countryʼs economy were discussed. At the stage of new development in our country, a number of reforms have been implemented to strengthen the legal, socio-economic foundations of ensuring gender equality in society, and it is appropriate to pay attention to the following in order to further expand the rights and opportunities of women and to increase the role of gender equality in society. passed.